Role of Maternal Education and Vaccination Coverage: Evidence From Pakistan Demographic and Health Survey. (November 2019) - Asif, Atta Muhammad; Akbar, Muhammad; Tahir, Muhammad Ramzan; Arshad, Irshad Ahmad
The aim of this study was to examine the impact of maternal education on child immunization uptake in Pakistan, both at individual and community levels. Pakistan Demographic and Health Survey data were used for analysis. Multilevel logistic regression was used to access the individual- and community-level factors associated with childhood immunization coverage. Out of 6765 children 2659 (39.3%) were fully immunized. Parents education, access to media, and wealth status have positive while ethnicity and working status of mother have a negative impact on the immunization uptake. In the community with a high percentage of educated mothers, the odds of immunized children were high (odds ratio = 1.43, 95% confidence interval = 1.14-1.80) as compared with communities with lower percentage of educated mothers. Moreover, significant variation was found in the likelihood of full immunization across communities. Both community- and individual-level factors have substantial impact on children immunization status. There is a need of improvement in maternal education, poverty alleviation, and removal of rural-urban disparities.